2010
DOI: 10.1108/17561371011017487
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and performance index of foreign direct investment in China's agriculture

Abstract: PurposeSince attracting foreign direct investment (FDI) to agriculture is now an important policy concern for the Chinese Government, it is necessary to develop benchmarks of the inward FDI performance. The purpose of this paper is to explore the determinants of FDI and evaluate the inward FDI performance in China's agriculture.Design/methodology/approachA multi‐variable regression model is conducted to examine the determinants of FDI in China's agriculture over the period from 1985 to 2006. In order to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…As mentioned earlier, most existing literature generally opine that FDI stock promotes GDP growth. On the other hand, however, a number of other studies indicate that rapid GDP growth rate is the most important determinants of the country's FDI inflows (Lv et al, 2010;Fung, 2004;and Berthelemy and Demurger, 2000). This implies the existence of a relationship between FDI inflows and GDP.…”
Section: Model Specification and Datamentioning
confidence: 98%
“…As mentioned earlier, most existing literature generally opine that FDI stock promotes GDP growth. On the other hand, however, a number of other studies indicate that rapid GDP growth rate is the most important determinants of the country's FDI inflows (Lv et al, 2010;Fung, 2004;and Berthelemy and Demurger, 2000). This implies the existence of a relationship between FDI inflows and GDP.…”
Section: Model Specification and Datamentioning
confidence: 98%
“…Studies at the industrial or sectoral level have been limited, especially the determinants of FDI in agricultural sector. Lv et al (2010) included agricultural market size, agricultural exports, agricultural imports, agricultural markets opening, and industrial policy as the main exogenous variables affecting agricultural FDI. While Abdul Rashid et al (2016) At the national investment level in Egypt, Bassiony (2017) examined some related agricultural variables such as agricultural market size, agricultural imports, agricultural exports, agricultural wages, agricultural savings, agricultural fiscal expenditure, agricultural lending and discount, and interest rate on agricultural lending and discount as the potential determinants of FDI in the agricultural sector.…”
Section: Literature 21 Agricultural Fdi Determinantsmentioning
confidence: 99%
“…Moreover, Mourao (2018) provided empirical evidence that population, forest area, exports diversification, and agriculture participation in GDP, inflation rates, real GDP per capita, government effectiveness, corruption perception, political stability, and regulatory quality were the economic factors that are determining the efficiency of Chinese's FDI in Africa. Lv et al (2010) found that the agricultural market size and agricultural imports were the most important factors in determining FDI inflows into china's agriculture. Abdul Rashid et al (2016) stated that GDP and poverty were the most important factors in determining FDI in agricultural sector in Malaysia, Oman and Brunei.…”
Section: Literature 21 Agricultural Fdi Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges of the micro-level analysis have led to the preference of the macro-level analysis of FDI. Among the studies that analysed the macro-determinants of FDI into China areBoermans et al (2009), Liu (2010),Kang & Wang (2011),Lv et al (2010) &Huang andWei (2010).…”
mentioning
confidence: 99%